Digital communication media and maternal health education: Integration of bibliometric analysis, methodological analysis, and meta-synthesis - Erry Yudhya Mulyani; Tri Rakhmawati; Sih Damayanti; Sik Sumaedi (Digital Health)
Introduction Information and communication technology advances have resulted in new communication channels, namely digital communication media, that can support maternal health education. Objective This study examines the current research situation on the use of digital communication media in the context of maternal health education. Methods The papers were collected from the Scopus database. Bibliometric analysis, methodological analysis, and meta-synthesis were performed to achieve the research objectives. Of the 426 papers, 316 were included in the filtering process (published in journals and English). A total of 98 papers were included in the analysis stage, with criteria that the paper must contain empirical studies, discuss digital communication media (maternal-health education), and the research subject is pregnant women. Results The bibliometric analysis results show the top authors (authors with the most publications and citations), top countries, top journals, top papers, and the research collaborations on the topic. The four theme groups in the meta-synthesis show that digital communication media has been widely utilized and is an effective tool for maternal health education. The USA, Australia, and Iran are the countries where most research is on digital communication media (maternal health education). The most researched digital communication media are mobile apps and social media. Most studies on this topic used a quantitative approach with experiments as a data collection procedure. Conclusion Several research gaps proposed in this study were exploring perceptions and acceptance of pregnant women regarding maternal health education, maternal education based on country context, and further research by considering the relevant theories.